Morphological re-description and molecular identification of Tabanidae (Diptera) in East Africa - Claire M. Mugasa; Jandouwe Villinger; Joseph Gitau; Nelly Ndungu; Marc Ciosi; Daniel Masiga (ZooKeys, 2018)
Biting flies of the family Tabanidae are important vectors of human and animal diseases across continents. However, records of Africa tabanids are fragmentary and mostly cursory. To improve identification, documentation and description of Tabanidae in East Africa, a baseline survey for the identification and description of Tabanidae in three eastern African countries was conducted. Tabanids from various locations in Uganda (Wakiso District), Tanzania (Tarangire National Park) and Kenya (Shimba Hills National Reserve, Muhaka, Nguruman) were collected. In Uganda, octenol baited F-traps were used to target tabanids, while NG2G traps baited with cow urine and acetone were employed in Kenya and Tanzania. The tabanids were identified using morphological and molecular methods. Morphologically, five genera (Ancala, Tabanus, Atylotus, Chrysops and Haematopota) and fourteen species of the Tabanidae were identified. Among the 14 species identified, six belonged to the genus Tabanus of which two (T. donaldsoni and T. guineensis) had not been described before in East Africa. The greatest diversity of tabanid species were collected from the Shimba Hills National Reserve, while collections from Uganda (around the shores of Lake Victoria) had the fewest number of species. However, the Ancala genus was found in Uganda, but not in Kenya or Tanzania. Maximum likelihood phylogenies of mitochondrial cytochrome c oxidase 1 (COI) genes sequenced in this study show definite concordance with morphological species identifications, except for Atylotus. This survey will be critical to building a complete checklist of Tabanidae prevalent in the region, expanding knowledge of these important vectors of human and animal diseases.